Using Star (Select, Teach, Activate and Revisit) Strategy to Increase Vocabulary Mastery of Eighth Grade Students - Supiah, Supiah; Defi, Defia Syntha (EEdJ: English Education Journal, 2021)
The objectives of this study were: (1) to describe the implementation of STAR (Select, Teach, Activate and Revisit) strategy of the eighth grade students of MTs N 1 Bangka, and (2) to find out whether there was any significant difference in vocabulary mastery between the students who were taught by using STAR strategy and the students who were taught without STAR strategy. This study was focused on vocabulary mastery. The total number of sample was 64 students. In this study, the researcher used experimental research method with a quasi-experimental design. The result showed that the students’ vocabulary mastery significantly increased. It could be seen from the pre-test and post-test mean score. Furthermore, the result of independent sample t-test of students’ post-test between experimental group and control group showed that the t-obtained was higher than t-table (2.547 > 2.00) and the p-output was lower than computation with level significant 0.05 (0.014 < 0.05). It means that the alternative hypothesis (Ha) was accepted and the null hypothesis (Ho) was rejected. It could be concluded that STAR strategy was effective to increase students’ vocabulary mastery.